Random Selection in Politics, Science and Society: Applications and Institutional Embeddedness - Bruno S. Frey; Lasse Steiner (Center for Research in Economics, Management and the Arts (CREMA), 2014)
This paper discusses and proposes random selection as a component in decision-making in society. Random procedures have played a significant role in history, especially in classical Greece and the medieval city-states of Italy. We examine the important positive features of decisions by random mechanisms. Random processes allow representativeness with respect to individuals and groups. They significantly reduce opportunities to influence political decisions by means of bribery and corruption and decrease the large expenses associated with today's democratic election campaigns. Random mechanisms can be applied fruitfully to a wide range of fields, including politics, the judiciary, the economy, science and the cultural sector. However, it is important that random selection processes are embedded in appropriately designed institutions.
Keywords: 330; Random selection; lot; democracy; representativeness; corruption